1994
DOI: 10.1016/0266-7681(94)90206-2
|View full text |Cite
|
Sign up to set email alerts
|

Lumbrical Muscle Incursion into the Carpal Tunnel During Finger Flexion

Abstract: Carpal tunnel syndrome is one of the many so-called cumulative trauma disorders thought by some to be related to the performance of repetitive tasks in the work-place. The cause of this disorder is unknown. We have observed lumbrical muscle incursion into the carpal tunnel during finger flexion. This study was conducted to determine the amount of this incursion in normal wrists. Five cadaver upper limbs were analyzed radiographically with radiopaque markers on the flexor retinaculum and the lumbrical muscle or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 11 publications
1
36
0
1
Order By: Relevance
“…A study by Cobb et al (1994) indicates that lumbricals incursion into the carpal tunnel during flexion is a normal occurrence. Another study by Cobb et al (1992) found a great deal of variation in the mass of lumbricals.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A study by Cobb et al (1994) indicates that lumbricals incursion into the carpal tunnel during flexion is a normal occurrence. Another study by Cobb et al (1992) found a great deal of variation in the mass of lumbricals.…”
Section: Discussionmentioning
confidence: 96%
“…A variety of congenital anatomical anomalies have been identified within the carpal tunnel by many investigators. There are also reports of lumbrical, muscles normally intrinsic to the hand, that hypertrophy to the point that a lumbrical will extend into the carpal tunnel even when the hand is in resting position (Cobb et al, 1994). Many of the studies examining variations and anomalies within the carpal tunnel focus on a single anatomical structure, however, such as the anatomical course of the median nerve and its branches, or an anomalous muscle belly.…”
Section: Introductionmentioning
confidence: 97%
“…Vibration and awkward postures are additional stressors that increase the risk of carpal tunnel syndrome. Normal lumbrical muscle incursion into the tunnel may also contribute to work-related CTS (114,115). Because the size of the tunnel may decrease, rheumatoid tenosynovitis, edema, pregnancy, and hypothyroidism have been identified as conditions that may contribute to the development of CTS.…”
Section: Risk Factors Of Carpal Tunnel Syndromementioning
confidence: 98%
“…The fourth proposed model assumes that the proximal ends of the lumbrical muscles may enter the distal end of the carpal tunnel as the flexor tendons upon which they originate move within the carpal tunnel in response to finger flexion [Cobb et al, 1994[Cobb et al, , 1995Yii and Elliot, 1994]. The increased contents within the carpal tunnel would increase intracarpal pressure and create mechanical contact pressure on the median nerve.…”
Section: Lumbrical Retractionmentioning
confidence: 98%
“…The tendons within the carpal tunnel are covered by one or tendon sheaths that may join to form a bursa. For some individuals, the proximal ends of the lumbrical muscles enter the distal end of the carpal tunnel, especially with digital flexion [Tanzer, 1959;Cobb et al, 1994;Yii and Elliot, 1994].…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%